Left Atrial Remodeling and Atrioventricular Coupling in a Canine Model of Early Heart Failure With Preserved Ejection Fraction. (October 2016) - Zakeri, Rosita; Moulay, Gilles; Chai, Qiang; Ogut, Ozgur; Hussain, Saad; Takahama, Hiroyuki; Lu, Tong; Wang, Xiao-Li; Linke, Wolfgang A.; Lee, Hon-Chi; Redfield, Margaret M.
Abstract : Background—: Left atrial (LA) compliance and contractility influence left ventricular stroke volume. We hypothesized that diminished LA compliance and contractile function occur early during the development of heart failure with preserved ejection fraction (HFpEF) and impair overall cardiac performance. Methods and Results—: Cardiac magnetic resonance imaging, echocardiography, left ventricular and LA pressure-volume studies, and tissue analyses were performed in a model of early HFpEF (elderly dogs, renal wrap-induced hypertension, exogenous aldosterone; n=9) and young control dogs (sham surgery; n=13). Early HFpEF was associated with LA enlargement, cardiomyocyte hypertrophy, and enhanced LA contractile function (median active emptying fraction 16% [95% confidence interval, 13–24]% versus 12 [10–14]%, P =0.008; end-systolic pressure-volume relationship slope 2.4 [1.9–3.2]mm Hg/mL HFpEF versus 1.5 [1.2–2.2]mm Hg/mL controls, P =0.01). However, atrioventricular coupling was impaired and the curvilinear LA end-reservoir pressure-volume relationship was shifted upward/leftward in HFpEF (LA stiffness constant [βLA ] 0.16 [0.11–0.18]mm Hg/mL versus 0.06 [0.04–0.10]mm Hg/mL controls; P =0.002), indicating reduced LA compliance. Impaired atrioventricular coupling and lower LA compliance correlated with lower left ventricular stroke volume. Total fibrosis and titin isoform composition were similar between groups; however, titin was hyperphosphorylated in HFpEF and correlated with βLA . LA microvascular reactivity was diminished in HFpEF versus controls. LA microvascular density tended to be lower in HFpEF and inversely correlated with βLA . Conclusions—: In early-stage hypertensive HFpEF, LA cardiomyocyte hypertrophy, titin hyperphosphorylation, and microvascular dysfunction occur in association with increased systolic and diastolic LA chamber stiffness, impaired atrioventricular coupling, and decreased left ventricular stroke volume. These data indicate that maladaptive LA remodeling occurs early during HFpEF development, supporting a concept of global myocardial remodeling. Abstract : Supplemental Digital Content is available in the text.